Search for excited τ-leptons and leptoquarks in the final state with τ-leptons and jets in pp collisions at s $$ \sqrt{s} $$ = 13 TeV with the ATLAS detector. (Tufts University. Tisch Library., 2023)
Keywords : Exotics, Hadron-Hadron Scattering.; Springer Open.